2022
DOI: 10.3390/land11060797
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Transportation Supply on Mixed Land-Use at the Parcel Level

Abstract: The interactive relationship between transportation and land use has become more difficult to understand and predict, due to the economic boom and corresponding fast-paced proliferation of private transportation and land-development activities. A lack of coordination between transportation and land-use planning has created an imbalanced provision of transportation infrastructure and land-use patterns; this is indicated by places where a high-density land-development pattern is supported by a low-capacity trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Well-planned transportation infrastructure facilitates the integration of diverse land use types, while MLU development increases transportation accessibility by reducing travel distances and promoting sustainable transportation alternatives. This symbiotic relationship contributes to the development of vibrant, connected, and sustainable communities [30,31]. For instance, Aygoren [32], suggests that if there are two primary uses, it should be classified as MLU.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Well-planned transportation infrastructure facilitates the integration of diverse land use types, while MLU development increases transportation accessibility by reducing travel distances and promoting sustainable transportation alternatives. This symbiotic relationship contributes to the development of vibrant, connected, and sustainable communities [30,31]. For instance, Aygoren [32], suggests that if there are two primary uses, it should be classified as MLU.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bhat et al [27] described accessibility as "the ease with which an individual can pursue an activity of a desired type, at a desired place, using a desired mode, and at a desired time." Accessibility is a primary focus of interdisciplinary research including transportation, health, economics, social sciences, urban studies, and geography [4,28]. The origins of spatial systems can be traced back to Tobler's law of geography, which states that "everything is connected to everything else, but nearby objects are more connected than distant things" [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The spatial accessibility of urban facilities has also improved significantly in TOD areas over time [ 36 ]. Similarly, Almansoub et al [ 37 ] conducted a study to evaluate the effect of accessibility on Mixed Land Use (MLU) at parcel level in the city of Wuhan, China. The study results showed a substantial relationship between the supply of public transportation and MLU.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accessibility has become of key importance in analytical measurements, and the literature is rich with accessibility applications [ 37 , 43 ]. It is important to understand the shortcomings and the theoretical concepts behind existing models for designing more robust accessibility models.…”
Section: Literature Reviewmentioning
confidence: 99%